OPTIMIZATION TYPE OF STIFFENING AGENT IN FORMULATION CREAM Melastoma malabathricum L. LEAF WATER FRACTION - Hasya Nadhira, Raden; Siska Anastasia, Desy; Apridamayanti, Pratiwi; Ropiqa, Meri (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
The skin is one of the visible outer parts of the body, and cosmetics are used for its care. Senggani (Melastoma malabathricum) leaves contain flavonoids, saponins, alkaloids, tannins, and polyphenols. The polyphenol content found in M. malabathricum leaves has high antioxidant activity and has the potential to be used as a sunscreen that can block the negative effects of UVA and UVB rays. These secondary metabolites can be obtained from the water fraction and used as antioxidants in cream preparations. Cream formulations require compounds that can maintain the consistency of the preparation to produce good physical properties and stability. This study aimed to analyze the type of stiffening agent in the formulation of cream preparation of aqueous fraction of senggani leaf (Melastoma malabathricum L.) using organoleptical tests, homogeneity, pH, spreadability, adhesiveness, and viscosity of cream preparation. The results showed that cetyl alcohol (FII) has different physical properties, and the evaluation and accelerated stability test (cycling test) resulted in the most physically stable preparation, as evidenced by the sig. (p value) > 0.05, indicating that storage did not affect the cream preparation.  Keywords: senggani leaf (Melastoma malabathricum L.), water fraction, cream, cycling test